Reculiarities of technological impact of construction machines used for pile foundation installation St. Petersburg - A. B. Ponomarev; D. A. Paskacheva; D. S. Korablev (Вестник СибАДИ, 2025)
Introduction. A characteristic feature of works on constructing the underground part of buildings or structures in the conditions of St. Petersburg is the significant thickness of weak clay soils. Such soils require gentle impact during various technological operations. The equipment used for constructing pile foundations can significantly affect the soil base and buildings in the area. The degree of construction machine impact is detected on completing construction works.Materials and methods. The article presents the main types of construction machines used for the construction of pile foundations in the conditions of St. Petersburg. A comparative analysis of technological parameters, advantages and disadvantages of various equipment has been performed. The engineering and geological conditions typical of St. Petersburg and the restrictions they impose on technologies for building pile foundations have been shown.Results. Examples of technological impact of various pile building methods on basements of the surrounding buildings and their structures in the conditions of St. Petersburg are given. A brief overview of soil conditions, machines and mechanisms, as well as potential risks of emergency situations is given.Discussion and conclusions. Conclusions have been made on most gentle methods of constructing pile foundations in conditions of weak clay soils and cramped urban development. Recommendations are given about the possibility of predicting the technological impact when constructing piles using numerical methods.